Recognizing the features of Isolated Fallopian Tube Torsion on CT and MRI and interobserver agreement: A cross-sectional study. Issue 157 (December 2022) - Coutureau, Juliette; Mandoul, Caroline; Curros-Doyon, Fernanda; Millet, Ingrid; Taourel, Patrice
Highlights: Isolated Fallopian tube torsion is a challenging diagnosis on imaging, as the ipsilateral ovary is usually of normal size and appearance. Two patterns of IFTT can easily be recognized on CT and MRI. Identification of a whirlpool sign, associated with either a hydrosalpinx or a para -ovarian cyst, is highly suggestive of the diagnosis. The knowledge of these findings may facilitate the preoperative diagnosis of IFTT in an emergency context. An early surgery is essential to avoid irreversible damages of the tube. Abstract: Purpose: Isolated Fallopian tube torsion (IFTT) is a rare cause of acute pelvic pain in women of reproductive age. Preoperative diagnosis is rarely made, even though an early surgery is necessary to preserve women's fertility. This study aims to identify simple and reproductible imaging features for the diagnosis of IFTT on sectional imaging. Methods: We conducted a retrospective, cross-sectional study on patients diagnosed with IFTT in our center between January 2008 and December 2021. The CTs and MRIs of 16 patients with surgically proven IFTT were retrospectively and independently reviewed by two radiologists to identify the relevant findings for the diagnosis. Results: The median patient age was 29 years (range: 13–63 years). Only four patients (25 %) had a conservatory treatment. Two patterns of IFTT were identified on CT and MRI. The first pattern (n = 6, 37 %) consisted of a thin-walled hydrosalpinx, U- or C-shaped, with a median diameter of 3 cm. The second pattern (n = 10, 63 %) consisted of an extra-ovarian cyst adjacent to a soft tissue mass containing the twisted tube and vessels. In 15 patients (94 %), the ipsilateral ovary was of normal size. Hematosalpinx was observed in 3 patients with necrosis of the tube on pathological reports (19 %). Interobserver agreement was substantial or good for all criteria. Conclusions: An association of simple and reproductible features can support the diagnosis of IFTT on sectional imaging in an emergency context: the identification of these features may avoid a delayed surgical treatment, which could otherwise compromise women's fertility.